Oxidative Stress Modulators and Functional Foods - Taira, Junsei (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book "Oxidative Stress Modulators and Functional Foods" is focused on the antioxidant role of natural products, involving their ability to modulate oxidative stress and/or reverse disease studied both in vitro and in animal models. Additionally, the molecular mechanisms of these actions and the modulation of signalling pathways related to inflammation, apoptosis, and survival response in the redox system by natural products are included.